Primary School Teachers’ Perspectives on Transformational Leadership and Academic Achievement - Vicent Kayombo; Rose Ephraim Matete; Majiyd Hamis Suru (UM Purwokerto Press, 2026)
Educational reforms emphasise leadership as a key driver of school effectiveness and improved learning outcomes among pupils. However, the implications of school leadership, particularly transformational leadership, for instructional improvement and pupil academic achievement in Tanzania remain unclear, despite ongoing policy interventions aimed at strengthening school leadership. This study is guided by the Path-Goal Theory, complemented by transformational leadership theory, to examine teachers’ experiences of transformational leadership and its implications for instructional improvement and pupil academic achievement. A convergent parallel mixed-methods design was employed, involving 382 participants. Of these, 356 primary school teachers were selected through simple random sampling, while 26 head teachers and Ward Education Officers were selected using purposive sampling. Data were collected through questionnaires and semi-structured interviews and analysed using inferential statistics and thematic analysis. The findings reveal that transformational leadership is widely practised and has a significant influence on teacher motivation, collaboration, and instructional practices, thereby indirectly enhancing pupil academic performance. However, inconsistencies in implementation were observed due to contextual constraints, such as limited leadership training and inadequate resources. The study recommends strengthening leadership capacity, enhancing institutional support, and promoting the consistent application of transformational leadership to improve teaching quality and learner outcomes.